Positive pole piece, preparation method thereof and dual-ion battery
By using a three-dimensional mesh-shaped conductive interlayer structure prepared by carbon fiber felt and thermal polymerization method in DIBs positive electrode materials, the problems of insufficient capacity and poor rate performance of existing DIBs positive electrode materials are solved, and the improvement of high capacity and rate performance is achieved.
Patent Information
- Application Number
- CN202411507727.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-28
- Publication Date
- 2025-02-07
AI Technical Summary
The existing dual-ion battery (DIBs) cathode materials have limited active sites and mismatched anion insertion, resulting in insufficient capacity and poor rate performance.
Using carbon fiber felt as the loading substrate, rigid polyion liquid (PEP-MIM) Cl and flexible high-conductive polymer PEDOT:PSS are closely combined through thermal polymerization to form a three-dimensional network-like conductive interlayer structure.
The embedded/exit layered structural voids of electrolyte anions are improved, the stability of the three-dimensional network conductive layered structure is enhanced, and the available capacity and rate performance of DIBs are improved.
Smart Images

Figure CN119400807A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of batteries, and in particular relates to a positive electrode plate and a preparation method thereof, and a dual-ion battery. Background Art
[0002] As energy and environmental issues become increasingly severe, the development of efficient, pollution-free, recyclable clean energy and energy storage devices has attracted much attention. Among various new energy storage devices, dual-ion batteries (DIBs) have gradually attracted great attention due to their low cost, environmental friendliness, and high operating voltage. Taking the typical dual-graphite DIBs charging and discharging process as an example, during the charging process, cations (such as Li + ) and anions (such as PF6 - ) are simultaneously inserted into the graphite anode and cathode, respectively, and during the discharge process, the inserted cations / anions migrate back to the electrolyte. Both cations and anions can serve as active materials in DIBs, thus enhancing the capacity of DIBs compared to lithium-ion batteries (LIBs). In particular, the insertion / deinsertion of anions in the positive electrode material usually occurs at high voltage, which is more conducive to improving the energy density.
[0003] DIBs usually use graphite materials as the positive electrode. Graphite has a unique layered structure composed of ABA-type hexagonal carbon rings, with weak interlayer interactions, which can allow the insertion / deinsertion of anions during the charge / discharge process. In addition, graphite is widely used in DIBs due to its low cost and good conductivity. However, due to the limited active sites of graphite and the large ionic radius of anions that does not match the interlayer spacing of graphite, when anions are embedded in graphite, it will cause volume expansion, resulting in problems such as insufficient specific capacity and poor rate performance of DIBs positive electrode materials.
[0004] Organic materials are environmentally friendly, recyclable, and designable (the structure can be adjusted according to design requirements), and show great potential in the field of energy storage. However, the organic conductive polymer segments are flexible, which will limit the uniform dispersion and adhesion of the slurry, thereby reducing the long-cycle stability of DIBs. The three-dimensional mesh conductive interlayer structure formed by polymerizing flexible conductive polymers with rigid polyionic liquids can promote the smooth embedding and extraction of a large number of anions. Applying it in the positive electrode of DIBs can rapidly improve the specific capacity and rate performance, and has good application prospects in the energy storage market.
[0005] The electrochemical performance of DIBs depends largely on the cathode material. Therefore, in order to obtain DIBs with high performance, high energy density and long cycle stability, it is of great significance to design, study and prepare polyionic liquid-based composite conductive polymer cathode materials of different types and structures. Summary of the invention
[0006] The purpose of the present invention is to overcome the shortcomings of the prior art and provide a positive electrode plate and a preparation method thereof and a dual-ion battery.
[0007] To achieve the above object, the technical solution adopted by the present invention is:
[0008] A positive electrode sheet, comprising a carbon fiber felt and a three-dimensional mesh conductive interlayer structure loaded on the surface of the carbon fiber felt; the three-dimensional mesh conductive interlayer structure comprises a rigid polyionic liquid and a flexible highly conductive polymer;
[0009] The rigid polyionic liquid is (PEP-MIM)Cl; the flexible high-conductive polymer is a mixture of poly(3,4-ethylenedioxythiophene) and poly(4-styrene sulfonic acid) PEDOT:PSS.
[0010] The molar ratio of the rigid polyionic liquid to the flexible highly conductive polymer is (1-2): (2:1); preferably 1:1;
[0011] The three-dimensional mesh conductive interlayer structure accounts for 2-5 mg·cm on the carbon fiber felt. -2 ; preferably 2 mg·cm -2
[0012] The rigid polyionic liquid is prepared by the following method: adding phthalic anhydride and N,N-dimethylformamide under inert conditions, and then adding epichlorohydrin to react to obtain PEP-Cl; adding N-methylimidazole to PEP-Cl to react, and adding acetone to the reaction product to separate and precipitate to obtain (PEP-MIM)Cl.
[0013] The present invention also includes a method for preparing the positive electrode sheet, comprising the following steps: first, mixing and stirring the EDOT monomer and the dopant PSS-Na to uniformly disperse them to obtain a mixed solution of EDOT and PSS, and soaking the treated carbon fiber felt in the mixed solution of (PEP-MIM)Cl, EDOT and PSS; then adding an initiator to react, and then adjusting the pH to acidic; finally, taking out the soaked carbon fiber felt and performing thermal polymerization to obtain a positive electrode sheet in which the (PEP-MIM)Cl-based composite PEDOT:PSS is polymerized on the surface of the carbon fiber felt.
[0014] The method for treating the carbon fiber felt is to use deionized water and ethanol to rinse and dry the carbon fiber felt.
[0015] The molar ratio of EDOT monomer to dopant PSS-Na is 1:(0.5-2.5); preferably 1:(2-2.5); more preferably 1:2.
[0016] The initiator is ammonium persulfate, and the amount of ammonium persulfate added is 0.05-0.5% of the mass of the EDOT monomer and PSS-Na, preferably 0.1%.
[0017] The present invention also includes a dual-ion battery, comprising the positive electrode sheet, the negative electrode sheet, the separator and the electrolyte.
[0018] The negative electrode sheet includes a negative electrode active material, a negative electrode binder and a negative electrode conductive agent; preferably, the negative electrode active material is graphite; the negative electrode conductive agent is CNT; the negative electrode binder is PVDF; preferably, the mass ratio of the negative electrode active material, the negative electrode binder and the negative electrode conductive agent is 8:1:1; preferably, the electrolyte includes a sodium salt and a solvent; the sodium salt is NaPF6; the solvent is a mixture of EC and DEC; the volume ratio of the two is 1:1; the concentration of the sodium salt is 0.5M.
[0019] Compared with the prior art, the present invention has the following beneficial effects:
[0020] The technical solution of the present application adopts a thermal polymerization method to prepare the positive electrode sheet. The method is simple and does not require a binder. (PEP-MIM)Cl and PEDOT:PSS can be tightly compounded to form a three-dimensional mesh conductive interlayer structure, which increases the layered structure gap for the insertion / extraction of electrolyte anions. Moreover, the π-π interaction between the benzene ring of (PEP-MIM)Cl and PEDOT:PSS, and the imidazole cation-π interaction greatly enhance the stability of the three-dimensional mesh conductive layered structure. At the same time, carbon fiber felt, as a loading substrate, increases the utilization rate of active sites and accelerates the insertion / extraction rate of ions.
[0021] In summary, based on the three-dimensional network conductive interlayer structure of (PEP-MIM)Cl-polymerized PEDOT:PSS, the bulky structural anions (such as PF6 - ) can be well inserted / deinserted into the cathode, thereby increasing the available capacity of DIBs and facilitating their widespread application in the production of commercial batteries. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 This is a schematic diagram of the structure of the positive electrode sheet according to an embodiment of the present invention;
[0023] Figure 2 It is a line graph of the conductivity data of the positive electrode sheets of materials 1-5 of the embodiments of the present invention;
[0024] Figure 3 Graph showing rate performance of batteries 1-10 according to embodiments of the present invention. DETAILED DESCRIPTION
[0025] In order to enable those skilled in the art to better understand the technical solution of the present invention, the present invention is further described in detail below in conjunction with the accompanying drawings and the best embodiments.
[0026] Example 1
[0027] A method for preparing a dual-ion battery comprises the following steps:
[0028] 1) Preparation of polyionic liquid (PEP-MIM) Cl using the following formula
[0029]
[0030] Specifically, the method comprises the following steps: (1) dehydrating and deoxygenating the reaction container; (2) adding phthalic anhydride and N,N-dimethylformamide (DMF) into the reaction container under nitrogen protection, and stirring to obtain a phthalic anhydride N,N-dimethylformamide solution; (3) adding ethylene glycol to the phthalic anhydride N,N-dimethylformamide solution obtained in step (2) under nitrogen protection, and stirring; (4) adding epichlorohydrin to the solution obtained in step (3), and reacting under stirring; (5) removing ( 4) adding N-methylimidazole to the remaining epichlorohydrin in the obtained reaction product, and reacting under stirring; (6) adding the reaction product obtained in (5) to acetone, stirring, and separating the solid and liquid to obtain a precipitate; (7) dissolving the precipitate obtained in (6) in deionized water, adding dropwise to a methyl orange aqueous solution, reacting under stirring, and separating the solid and liquid of the reaction product to obtain a precipitate; (8) repeatedly washing the precipitate obtained in (7) with deionized water, and vacuum drying to obtain a polyionic liquid (PEP-MIM)Cl.
[0031] 2) Preparation of positive electrode sheet: First, EDOT monomer and dopant PSS-Na (n(EDOT): n(PSS) = 1: 2.5) were mixed and stirred for 30 minutes to make them evenly dispersed. At the same time, the carbon fiber felt was treated with deionized water and ethanol. According to the above steps, the prepared (PEP-MIM)Cl was placed in a container, and the treated carbon fiber felt was placed in a mixed solution of (PEP-MIM)Cl, EDOT and PSS for 30 minutes. Then, 0.1wt% EDOT:PSS APS was added to the container, and then HCl was added until the pH of the environment was 5. Finally, the soaked carbon fiber felt was taken out and placed in an oven, and the oven temperature was set to 100°C for 3 hours. After the reaction was completed, it was cooled to room temperature to obtain a positive electrode sheet of material 1 (PEP-MIM)Cl-based composite PEDOT:PSS polymerized on the surface of CFs. The molar ratio of polyionic liquid (PEP-MIM) Cl and conductive polymer PEDOT:PSS is 1:1, and the content of polyionic liquid (PEP-MIM) Cl and conductive polymer PEDOT:PSS in carbon fiber felt is 2 mg cm-2 The schematic diagram of the positive electrode of material 1 is as follows Figure 1 The conductivity data are shown in Table 1 and Figure 2 .
[0032] 3) Preparation of dual-ion battery: dual-ion battery electrolyte was prepared according to the ratio of 0.5M NaPF6 / EC:DEC=1:1vol%, and negative electrode plate was prepared according to the weight ratio of graphite:CNT:PVDF of 8:1:1. Using the above positive electrode plate, dual-ion battery electrolyte, PP separator and negative electrode plate, CR2032 button battery was assembled in a glove box, numbered as battery 1. Battery 1 was tested for charge and discharge cycles at 25°C with a current of 1C and a voltage of 2.0-4.0V. The charge and discharge cycle test data of the battery are shown in Table 2, and the rate diagram of the battery is shown in Figure 3 .
[0033] Example 2
[0034] The only difference between Example 2 and Example 1 is that the molar ratio of EDOT monomer and dopant PSS-Na in step 2) is different, n(EDOT):n(PSS)=1:2.
[0035] Example 3
[0036] The only difference between Example 3 and Example 1 is that the molar ratio of EDOT monomer and dopant PSS-Na in step 2) is different, n(EDOT):n(PSS)=1:1.5.
[0037] Example 4
[0038] The only difference between Example 4 and Example 1 is that the molar ratio of EDOT monomer and dopant PSS-Na in step 2) is different, n(EDOT):n(PSS)=1:1.
[0039] Example 5
[0040] The only difference between Example 5 and Example 1 is that the molar ratio of EDOT monomer and dopant PSS-Na in step 2) is different, n(EDOT):n(PSS)=1:0.5.
[0041] Example 6
[0042] The only difference between Example 6 and Example 2 is that in step 2), the content of polyionic liquid (PEP-MIM) Cl and conductive polymer PEDOT:PSS in carbon fiber felt is 5 mg·cm -2 .
[0043] Comparative Example 1
[0044] The difference between Comparative Example 1 and Example 1 is that the preparation method of the positive electrode sheet is different, and the following steps are specifically adopted: EDOT monomer and dopant PSS (n(EDOT):n(PSS)=1:2) are dispersed in N-methylpyrrolidone (NMP), mixed and stirred for 30 minutes, transferred to a reactor, vacuum reacted at 180°C for 10 hours, cooled to room temperature and filtered to obtain solid powder, and material 7PEDOT:PSS positive electrode material can be obtained. The positive electrode sheet is prepared according to the weight ratio of material 7:CNT:PVDF of 90:5:5.
[0045] Comparative Example 2
[0046] The difference between Comparative Example 2 and Example 1 is that the preparation method of the positive electrode sheet is different. Specifically, the following steps are adopted: dissolve the graphite positive electrode active material, CNT, PVDF, etc. in NMP solvent, stir evenly, apply it on the surface of carbon fiber felt, dry it at 120°C for 2h, cool it to room temperature, and stand it for 8h to obtain the positive electrode sheet on the surface of material 8 graphite-loaded carbon fiber felt. The graphite content of carbon fiber felt is 2mg·cm -2 .
[0047] Example 7
[0048] The only difference between Example 7 and Example 2 is that in step 2), the molar ratio of the polyionic liquid to the conductive polymer PEDOT:PSS is 1:2.
[0049] Example 8
[0050] The only difference between Example 8 and Example 2 is that in step 2), the molar ratio of the polyionic liquid to the conductive polymer PEDOT:PSS is 2:1.
[0051] Table 1 shows the conductivity data of the positive electrode sheets of materials 1-5, and Table 2 shows the comparison of the electrochemical performance of batteries 1-8. The test methods are well-known in the art and will not be described in detail.
[0052] Table 1. Conductivity data of positive electrode sheets of materials 1-5 of the present invention
[0053]
[0054] Table 2. 1C battery cycle data of the embodiments of the present invention and the comparative examples
[0055]
[0056]
[0057] As can be seen from Table 1, with the increase in the amount of PSS-Na, the number of sulfonic acid groups will also increase, resulting in better doping effect, higher conductivity, and more PEDOT adsorption. When the PSS / EDOT molar ratio is greater than 2, the conductivity shows a downward trend. This is because with the increase in the amount of PSS, the acidity of the reaction system is too high and PSS occupies a large space, which hinders the transfer of electrons in PEDOT; at the same time, the viscosity of the reaction system increases, which is not conducive to the polymerization of PEDOT on the carbon fiber felt. Figure 1 This is a line graph of the conductivity data of the positive electrode sheets of materials 1-5, and the pattern is the same as above.
[0058] It can be seen from Table 2 that battery 2 has the best performance. The mixing ratio of conductive polymer DOET and dopant PSS in material 2 is 1:2, and the conductivity is the best. The molar ratio of polyionic liquid (PEP-MIM) Cl and conductive polymer PEDOT:PSS is 1:1, and the content of polyionic liquid (PEP-MIM) Cl and conductive polymer PEDOT:PSS in carbon fiber felt is 2 mg cm -2 . Carbon fiber felt provides excellent self-supporting performance. Based on the stability of the three-dimensional mesh conductive interlayer structure of the polyionic liquid-based conductive polymer, the positive electrode sheet prepared by material 2 has excellent long-cycle stability, conductivity and high specific capacity. Therefore, the technical method of the present invention is adopted to polymerize the rigid polyionic liquid and the flexible conductive polymer on the carbon fiber felt by thermal polymerization. The synthesized positive electrode sheet is used in DIBs, which is more conducive to obtaining DIBs with high cycle stability, high specific capacity and low cost.
[0059] Figure 3 This is a graph of battery 1-10 rate performance. It can be seen from the graph that battery 2 has the best performance. The rate performance of material 2 at 0.2C, 0.5C, 1C and 5C is combined with the advantages of the three-dimensional mesh conductive interlayer structure (PEP-MIM) Cl-co-PEDOT:PSS / CFs, and battery 2 has the best overall rate performance.
[0060] In summary, the technical solution of the present application adopts a thermal polymerization method to prepare the positive electrode sheet. The method is simple, does not require a binder, and can tightly compound (PEP-MIM)Cl with PEDOT:PSS to form a three-dimensional mesh conductive interlayer structure, which increases the layered structure gap for the insertion / extraction of electrolyte anions. Moreover, the π-π interaction between the benzene ring of (PEP-MIM)Cl and PEDOT:PSS, and the imidazole cation-π interaction greatly enhance the stability of the three-dimensional mesh conductive layered structure. At the same time, carbon fiber felt, as a loading substrate, increases the utilization rate of active sites and accelerates the insertion / extraction rate of ions.
[0061] In summary, based on the three-dimensional network conductive interlayer structure of (PEP-MIM)Cl-polymerized PEDOT:PSS, the bulky structural anions (such as PF6 - ) can be well inserted / deinserted into the cathode, thereby increasing the available capacity of DIBs and facilitating their widespread application in the production of commercial batteries.
[0062] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A positive electrode sheet, characterized in that: It includes a carbon fiber felt and a three-dimensional mesh conductive interlayer structure loaded on the surface of the carbon fiber felt; the three-dimensional mesh conductive interlayer structure includes a rigid polyionic liquid and a flexible highly conductive polymer; The rigid polyionic liquid is (PEP-MIM)Cl; the flexible high-conductive polymer is a mixture of poly(3,4-ethylenedioxythiophene) and poly(4-styrene sulfonic acid) PEDOT:PSS.
2. The positive electrode sheet according to claim 1, characterized in that: The molar ratio of the rigid polyionic liquid to the flexible highly conductive polymer is (1-2):(2:1); preferably 1:
1.
3. The positive electrode sheet according to claim 1, characterized in that: The three-dimensional mesh conductive interlayer structure accounts for 2-5 mg·cm on the carbon fiber felt. -2 ; preferably 2 mg·cm -2 .
4. The positive electrode sheet according to claim 1, characterized in that: The rigid polyionic liquid is prepared by the following method: adding phthalic anhydride and N,N-dimethylformamide under inert conditions, and then adding epichlorohydrin to react to obtain PEP-Cl; adding N-methylimidazole to PEP-Cl to react, and adding acetone to the reaction product to separate and precipitate to obtain (PEP-MIM)Cl.
5. A method for preparing a positive electrode sheet according to any one of claims 1 to 4, characterized in that: The method comprises the following steps: firstly, EDOT monomer and dopant PSS-Na are mixed and stirred to be evenly dispersed to obtain a mixed solution of EDOT and PSS, and the treated carbon fiber felt is placed in the mixed solution of (PEP-MIM)Cl, EDOT and PSS for immersion; then an initiator is added for reaction, and then the pH is adjusted to be acidic; finally, the soaked carbon fiber felt is taken out and thermally polymerized to obtain a positive electrode sheet in which (PEP-MIM)Cl-based composite PEDOT:PSS is polymerized on the surface of the carbon fiber felt.
6. The method for preparing a positive electrode sheet according to claim 5, characterized in that: The method for treating the carbon fiber felt is to use deionized water and ethanol to rinse and dry the carbon fiber felt.
7. The method for preparing a positive electrode sheet according to claim 5, characterized in that: The molar ratio of EDOT monomer to dopant PSS-Na is 1:(0.5-2.5); preferably 1:(2-2.5); more preferably 1:
2.
8. The method for preparing a positive electrode sheet according to claim 5, characterized in that: The initiator is ammonium persulfate, and the amount of ammonium persulfate added is 0.05-0.5% of the mass of the EDOT monomer and PSS-Na, preferably 0.1%.
9. A dual-ion battery, characterized in that: It comprises the positive electrode sheet, negative electrode sheet, separator and electrolyte as described in any one of claims 1 to 4.
10. The dual ion battery according to claim 9, characterized in that: The negative electrode sheet includes a negative electrode active material, a negative electrode binder and a negative electrode conductive agent; preferably, the negative electrode active material is graphite; the negative electrode conductive agent is CNT; the negative electrode binder is PVDF; preferably, the mass ratio of the negative electrode active material, the negative electrode binder and the negative electrode conductive agent is 8:1:1; preferably, the electrolyte includes a sodium salt and a solvent; the sodium salt is NaPF6; the solvent is a mixture of EC and DEC; the volume ratio of the two is 1:1; the concentration of the sodium salt is 0.5M.